PERAN KOMUNIKASI SUAMI ISTRI DALAM MEWUJUDKAN KEHARMONISAN KELUARGA DI GEREJA BETHEL INDONESIA TABGHA BATAM - Tahan Sitanggang; George Rudi Hartono Pasaribu; Steven Steven (JURNAL IMPARTA, 2023)
Marriage is the first institution God creted on this earth. Communication is a very vital factor in a healthy marriage between man and woman as they together build a Christian family. Communication after a couple has just gotten married gives them many challenges as they try to fit their lives together, with each coming from different background and having different expectations for how they will live and work together. Even after several years of marriage they still need to have open communication between them. They need to learn about healthy ways of communicating with each other. A harmonious marriage is usually marked by good communication between husband and wife, because through good communication a husband and wife can know and understand their partner. This study uses quantitative methods based on quantification in data collection and analysis to test the established hypotheses. Conducted at the Indonesia Tabgha. Church is very evident This method can be said to have succeeded in realizing them that a marriage becomes a strong marriage, if both the bride and groom make careful and thorough preparations. Careful means both have the ability to anticipate various things that will arise from the marriage. Mature in the sense that both of them are willing to work together in growing enthusiasm, comfortable, willing and without coercion at all in entering the gates of Christian marriage.Following up on the results of the study, the researcher proposes several programs and it is hoped that these proposed programs can be a solution in improve marital harmony at Bethel Church of Indonesia Tabgha Batam.